Studi Literatur Perbandingan Performa Reproduksi Kuda Betina Lokal (Equus cabballus) dan Kuda Turunan Thoroughbred - Loak, Rut Elisabet; Gaina, Cynthia D; Tophianong, Tarsisius C (Jurnal Veteriner Nusantara, 2024)
A horse is a creature that offers several advantages to people, including use as a mode of transportation, a means of cargo transit, a source of power to pull wagons or carts, a source of sustenance like meat and milk, as well as in sporting arenas and as equestrian cavalry. Indonesians enjoy participating in horse racing as one of their favorite equestrian sports, hence efforts are being made to improve the genetic quality of local horses by breeding them with Thoroughbreds to create Indonesian racehorses . In order to assess the reproductive efficiency of local thoroughbred mares and to ascertain the first mating age, gestational age, service per conception, and foaling interval in local thoroughbred mares, a literature review was conducted. The goal of doing a literature review was to evaluate the reproductive efficiency of nearby thoroughbred mares, as well as their first mating age, gestational age, time between conceptions, and foaling interval. Using the Mendeley and Google Scholar programs, a variety of reference sources were gathered for this literature study. The findings of the reproductive performance of local horses and thoroughbred breeds as observed from the age of first mating, length of gestation, Foaling interval, and S/C of local horses and thoroughbred horses varied but remained within the normal range. Genetics, training methods, the environment, the type of feed, and the purpose for which the horses are kept all have an impact on this.